Factors Affecting Employee Performance - Husen, Rahmatia; Hasyim, Abd. Wahab; Marwan, Marwan (AIBPM Publisher, 2024)
This study investigates the factors that influence employee performance, namely personal factors, leadership, co-worker factors, work facilities, and work environment. This study uses a quantitative explanatory approach with primary data obtained from a survey with a questionnaire. The population in this study were all employees in North Maluku Province. The sample in the study came from two agencies, namely the Communication, Informatics, and Code Agency and the Transportation Agency of North Maluku Province, totaling 103 people. The data analysis technique used multiple regression with the help of SPSS software. The findings indicate that personal factors and leadership positively influence employee performance, with improved individual attributes and effective leadership leading to enhanced performance outcomes. Conversely, the presence of a larger number of co-workers was found to negatively affect performance, potentially due to role ambiguity and reduced accountability. Additionally, work facilities and the work environment did not significantly impact employee performance. The results emphasize the importance of focusing on personal and leadership development to boost employee effectiveness while addressing co-worker dynamics to maintain clear roles and responsibilities. Future research should further investigate these relationships to refine strategies for organizational performance improvement.